THE EFFECT OF HEALTH EDUCATION USING QUARTET FLASHCARD MEDIA ON ELEMENTARY SCHOOL CHILDREN’S KNOWLEDGE OF DIARRHEA PREVENTION IN TASIKMALAYA - Yanti, Tasya Dwi; Falah, Miftahul; Solihatin, Yuyun; Muttaqin, Zainal (Universitas Muhammadiyah Ponorogo, 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among children, particularly in developing countries. Poor hygiene awareness and limited knowledge about prevention are major contributing factors. Health education using interactive media, such as the Quartet Card, can enhance children's understanding of diarrhea prevention.This study aimed to assess the effectiveness of health education using the Quartet Card in improving elementary school students' knowledge of diarrhea prevention. This study employed a pre-experimental design using a one-group pretest-posttest approach to evaluate the effectiveness of the intervention. The sample consisted of 55 students from SDN 7 Singaparna, Tasikmalaya Regency, selected through total sampling. The Wilcoxon Signed Rank Test results showed a p-value of 0.000 (p < 0.05), indicating a significant improvement in students' knowledge after the intervention. Therefore, health education using Quartet Card media has been proven effective in enhancing students' knowledge of diarrhea prevention. This educational tool presents information in a visually engaging format through card-based games that promote active participation, discussion, and repetition. Such an approach creates a fun and interactive learning experience, making it easier for students to comprehend and retain information related to clean and healthy living behaviors.